2015
DOI: 10.4081/ejh.2015.2482
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-mediated endocytosis of lysozyme in renal proximal tubules of the frog Rana temporaria

Abstract: The mechanism of protein reabsorption in the kidney of lower vertebrates remains insufficiently investigated in spite of raising interest to the amphibian and fish kidneys as a useful model for physiological and pathophysiological examinations. In the present study, we examined the renal tubular uptake and the internalization rote of lysozyme after its intravenous injection in the wintering frog Rana temporaria using immunohisto- and immunocytochemistry and specific markers for some endocytic compartments. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
(93 reference statements)
1
6
0
4
Order By: Relevance
“…Data on similar experiments on cellular uptake of lysozyme are scarce, but recent in vivo studies reported on absorption of lysozyme in the intestinal tract [49], which appears to be occurring by non-saturable and saturable processes, the latter pointing to an involvement of endocytic pathway(s). Furthermore, it has recently been suggested that receptor-mediated endocytosis of lysozyme in renal proximal tubules may be mediated by megalin and cubilin [50]; the mRNA expression, although at a very low level, of the latter receptor was confirmed in the cell model used in this study. Furthermore it should be noted that complexation of lysozyme with non-targeted copolymers resulted in similar level of internalization as for 'free' lysozyme (Fig.…”
Section: Cellular Internalization Of B 12 -Targeted Protein-polymer Complexes In Vitrosupporting
confidence: 70%
“…Data on similar experiments on cellular uptake of lysozyme are scarce, but recent in vivo studies reported on absorption of lysozyme in the intestinal tract [49], which appears to be occurring by non-saturable and saturable processes, the latter pointing to an involvement of endocytic pathway(s). Furthermore, it has recently been suggested that receptor-mediated endocytosis of lysozyme in renal proximal tubules may be mediated by megalin and cubilin [50]; the mRNA expression, although at a very low level, of the latter receptor was confirmed in the cell model used in this study. Furthermore it should be noted that complexation of lysozyme with non-targeted copolymers resulted in similar level of internalization as for 'free' lysozyme (Fig.…”
Section: Cellular Internalization Of B 12 -Targeted Protein-polymer Complexes In Vitrosupporting
confidence: 70%
“…In our studies, the expression of endocytic receptors in PT cells of the frog mesonephros was revealed after injections of YFP [18] and lysozyme [17] using polyclonal antibodies against megalin and cubilin. In 15-30 min, absorbed YFP was colocalized with immunolabeled megalin or cubilin in apical endocytic vesicles (Figure 4A-D).…”
Section: Molecular and Cellular Mechanisms Of Endocytosis In The Amphmentioning
confidence: 86%
“…Earlier, intestinal absorption and the resulting accumulation of these fluorescent proteins in renal PTs after their intragastric administration were established [16]. Later, the uptake of lysozyme in the amphibian kidney was also demonstrated [17]. Some examples of tubular reabsorption of abovementioned proteins in amphibians and rats are shown below (Figure 2).…”
Section: Structural and Functional Basis Of Glomerular Filtration Andmentioning
confidence: 97%
See 1 more Smart Citation
“…Although these changes are not specific for lysozyme-induced tubular injury, enlarged proximal tubular lysosomes are common in CMML nephropathy [ 6 , 8 ]. It is known that proximal tubular cells absorb lysozyme via endocytosis to degrade in lysosomes [ 10 , 11 ]. We think that lysosomes in the proximal tubular cells were processing overloaded lysozyme both in CMML and sarcoidosis.…”
mentioning
confidence: 99%